Potential Defects and Improvements of Equivalent Uniform Dose Prediction Model Based on the Analysis of Radiation-Induced Brain Injury - Du, Qing-Hua; Li, Jian; Gan, Yi-Xiu; Zhu, Hui-Jun; Yue, Hai-Ying; Li, Xiang-De; Ou, Xue; Zhong, Qiu-Lu; Luo, Dan-Jing; Xie, Yi-Ting; Liang, Qian-Fu; Wang, Ren-Sheng; et al. (Frontiers in Oncology, 2022)
Purpose: To study the impact of dose distribution on volume-effect parameter and predictive ability of equivalent uniform dose (EUD) model, and to explore the improvements. Methods and Materials: The brains of 103 nasopharyngeal carcinoma patients receiving IMRT were segmented according to dose distribution (brain and left/right half-brain for similar distributions but different sizes; VD with different D for different distributions). Predictive ability of EUDVD (EUD of VD) for radiation-induced brain injury was assessed by receiver operating characteristics curve (ROC) and area under the curve (AUC). The optimal volume-effect parameter a of EUD was selected when AUC was maximal (mAUC). Correlations between mAUC, a and D were analyzed by Pearson correlation analysis. Both mAUC and a in brain and half-brain were compared using paired samples t-tests. The optimal DV and VD points were selected for a simple comparison. Results: The mAUC of brain/half-brain EUD was 0.819/0.821 and the optimal a value was 21.5/22. As D increased, mAUC of EUDVD increased and a decreased. The mAUC reached maximum when D was 50-55Gy, and a was always 1 when D≥55Gy. The difference of mAUC/a between brain and half-brain was not significant. In the a range of 1 to 22, AUC of EUDV55Gy in brain/half-brain (0.857-0.830/0.845-0.830) was always larger than that of EUD (0.681-0.819/0.691-0.821). The AUCs of optimal dose/volume points were 0.801 (brain D2.5cc), 0.823 (brain V70Gy), 0.818 (half-brain D1cc) and 0.827 (half-brain V69Gy), respectively. Mean dose (equal to EUDVD with a=1) of high-dose volume (V50Gy-V60Gy) was superior to traditional EUD and dose/volume points. Conclusion: Volume-effect parameter of EUD is variable and related to dose distribution. EUD with large low-dose volume may not be better than simple dose/volume points. Critical-dose-volume EUD could improve the predictive ability and has an invariant volume-effect parameter. Mean dose may be the case in which critical-dose-volume EUD has the best predictive ability.